Efficacy of Osteoporosis Drugs Anabolic and Antiresorptive Classes in Post Menopause Women - Ribka Carolin; Basuki Supartono; Yanto Sandy Tjang (Universitas Muhammadiyah Malang, 2021)
Osteoporosis is a degenerative bone disease that affects many postmenopausal women. Antiosteoporosis drugs consist of antiresorptive and anabolic groups. So far, there is still controversy over the administration of antiosteoporosis drugs, therefore researchers conducted a systematic review study aimed at determining which one is more effective. This research was conducted by reviewing several studies through the PubMed and Science Direct databases. The results showed that abaloparatide, teriparatide, and SERM (Selective Estrogen Receptor Modulators) were more effective than bisphosphonates. In conclusion, the anabolic class is more effective than the antiresorptive class in postmenopausal women.